2022
DOI: 10.3390/ijerph192316135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Air Cleaning Device Equipped with Filtration and UV: Comparison of Removal Efficiency on Particulate Matter and Viable Airborne Bacteria in the Inlet and Treated Air

Abstract: Since the COVID-19 pandemic, improving indoor air quality (IAQ) has become vital for the public as COVID-19 and other infectious diseases can transmit via inhalable aerosols. Air cleaning devices with filtration and targeted pollutant treatment capabilities can help improve IAQ. However, only a few filtration/UV devices have been formally tested for their effectiveness, and little data is publicly available and UV doses comparable. In this research, we upgraded a particulate matter (PM) air filtration prototyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Li et al [2] improved air filtration with UV-C lamps to effectively neutralise airborne pathogens, especially SARS-CoV-2. They refined UV-C dose calculations and performed radiation tests.…”
Section: Included Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [2] improved air filtration with UV-C lamps to effectively neutralise airborne pathogens, especially SARS-CoV-2. They refined UV-C dose calculations and performed radiation tests.…”
Section: Included Articlesmentioning
confidence: 99%
“…Among the experimental studies [1,2,[12][13][14]17,22,23,25,29,31,40,43,44,46,48,49,52,[54][55][56][57][60][61][62][63][64]70,71], three [12,13,23] performed tests in work or everyday living environments, while [1,2,15,29,48,49,54,56,60,70] performed tests in test chambers. Some papers [14,17,25,43,44,52,[62][63][64]…”
Section: Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in light of the COVID-19 pandemic, Qiao et al tested a smaller-scale UV-C duct unit and concluded that the unit can achieve greater than 2-log reduction in viable coronavirus inactivation with a flow rate of 2,439 L min −1 ( 126 ). Since UV-C light itself does not capture or remove pathogens from the fluid stream, it is often used as an additional device to augment current HVAC systems with filters ( 127 ); it is commonly available commercially for this purpose. Importantly, during filter disinfection, the filters still collect pathogens and the time of UV-C exposure is increased for collected pathogens, thus the UV-C intensity can be reduced as compared to that needed for standalone ducted systems.…”
Section: Control Technologies Overviewmentioning
confidence: 99%
“…This is most likely due to the reality that emerging air disinfection techniques have not been yet trialled for their efficiency in real life settings. Recently, here have been advanced prototype investigations into air disinfection using UV-C techniques with providing good results [18] Advanced HVAC-integrated air purification systems have been reported in comparative studies, and these have seen a reduction in hospital stays [19,20]. Arikan et al reported a reduction in surface microbial levels following air treatment in an intensive care unit [21].…”
mentioning
confidence: 99%